STUDI PENCIPTAAN MULTIMEDIA KERIS DENGAN KONSEP ANIMASI EDUKASI - Rahman, Anung (Acintya, 2010)
The multimedia applicatiton, its aesthetic, and its contents are threechotomy which is inherent to theÂ interractive education planning. All of these must be have an equal function if a developer wish to have anÂ optimal results to the education process. This research will explore the keris as a multimedia materialapplied to the education process. This also contains an applied creation which is combine between kerisÂ education 's contents and an aesthetic of multimediaa material. The creation of â€œkeris multimedia material"Â is not only given to the information purposes, but it also to have a contents in what kind of edutaive eï¬ectwill working by using humanism approach. Educative applied materials are presented by diï¬erent ways,Â because of it especially seen into the aesthetic media applied.Key words: multimedia, education, keris.